2020
DOI: 10.1101/2020.11.04.20225888
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Point-of-care detection of SARS-CoV-2 in nasopharyngeal swab samples using an integrated smartphone-based centrifugal microfluidic platform

Abstract: With its origin estimated around December 2019 in Wuhan, China, the ongoing 2020 SARS-CoV-2 pandemic is a major global health challenge, resulting in more than 45 million infections and 1.2 million deaths. The demand for scalable, rapid and sensitive viral diagnostics is thus particularly pressing at present to help contain the rapid spread of infection and prevent overwhelming the capacity of health systems. While high-income countries have managed to rapidly expand diagnostic capacities, such is not the case… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…This detection limit is significantly lower than recent published studies describing LAMP in microdevices for the diagnosis of COVID-19. 20,43,44 The low detection limit found in this study is due to the fact that the use of SYBR Green leads to increased sensitivity when compared with others detection method. 47 However, the inhibitory effect of SYBR Green on the LAMP reaction is well established.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…This detection limit is significantly lower than recent published studies describing LAMP in microdevices for the diagnosis of COVID-19. 20,43,44 The low detection limit found in this study is due to the fact that the use of SYBR Green leads to increased sensitivity when compared with others detection method. 47 However, the inhibitory effect of SYBR Green on the LAMP reaction is well established.…”
Section: Discussionmentioning
confidence: 81%
“…Currently, some studies have reported the molecular detection of SARS-CoV-2 by LAMP in tubes with a limit of detection of 0.1-10 copies per µL. 41,42 A recently published study by Soares et al 20 reported a LAMP assay performed on a PMMAbased microfluidic platform with a detection limit of 10 2 -10 3 copies per reaction and an analysis time of 30 min. Rodriguez-Manzano and coworkers 43 described a LAMP assay in a cartridge microfluidic device for the detection of SARS-CoV-2 RNA samples showing a limit of detection of 10 RNA copies per reaction in under 20 minutes.…”
Section: Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Two microfluidic systems based on centrifugal liquid flow have been reported. With the objective of simplifying the sample processing step, Soares et al (2020) developed an integrated smartphone-enabled, centrifugal, microfluidic platform for a sample-to-result fluorescence-based RT-LAMP test. Using modified agarose beads, their device enhances the signal specificity and mitigates the effect of collection medium on weakly buffered colorimetric LAMP assays ("Considerations for pH-Based Colorimetric RT-LAMP").…”
Section: Nanofabricated Channel Based-microfluidic Devicesmentioning
confidence: 99%
“…Soares et al have used LAMP for the detection of SARS-CoV-2 on a centrifugal platform using agarose beads for signal enhancement after nucleic acid amplification. 38 Their system can detect 100 to 1000 RNA copies in a 10 μL reaction volume based on fluorescence read-out using a simple optical set-up and a smartphone camera. More recently, de Oliveira et al have developed a low-cost centrifugal device made of polystyrene-toner that is operated on a fidget-spinner for molecular diagnosis of SARS-CoV-2 RNA (prepared off-chip) using RT-LAMP.…”
Section: Introductionmentioning
confidence: 99%